Evaluation of bioactive glass and hydroxyapatite crystals as pulpotomy agents in primary molars: A clinical study - Neeraja Govindaraj; Kinjal Shah; Priya Subramaniam; Megha Gupta (Arbu Academic Publishing, 2020)
Aim: To clinically and radiographically evaluate the potential of bioactive glass and hydroxyapatite crystals as pulpotomy agents in primary molars. Methods: A total of fifty teeth were selected from 25 children (14 boys and 11 girls) aged 4 to 9 years, who had no medical condition that would contraindicate pulp therapy. Each child had at least two primary molars (first and/or second primary molar) requiring pulpotomy. A conventional pulpotomy procedure was performed on the selected teeth using bioactive glass and hydroxyapatite crystals. All molars were evaluated clinically and radiographically at regular intervals over 12 months. The results were subjected to statistical analysis using Fischer exact test. Results: One hundred percent clinical success and 84% radiographic success was observed in both the groups at the end of the study period. Conclusions: The study concluded that both bioactive glass and hydroxyapatite crystals can be used as pulpotomy agents in primary molars.